Hepatic macrophages: Key players in the development and progression of liver fibrosis. (24th May 2021) - Cheng, Da; Chai, Jin; Wang, Huiwen; Fu, Lei; Peng, Shifang; Ni, Xin
Abstract: Hepatic fibrosis is a common pathological process involving persistent liver injury with various etiologies and subsequent inflammatory responses that occur in chronic liver diseases. If left untreated, liver fibrosis can progress to liver cirrhosis, hepatocellular carcinoma and eventually, liver failure. Unfortunately, to date, there is no effective treatment for liver fibrosis, with the exception of liver transplantation. Although the pathophysiology of liver fibrosis is multifactorial and includes the activation of hepatic stellate cells, which are known to drive liver fibrogenesis, hepatic macrophages have emerged as central players in the development of liver fibrosis and regression. Hepatic macrophages, which consist of resident macrophages (Kupffer cells) and monocyte‐derived macrophages, have been shown to play an intricate role in the initiation of inflammatory responses to liver injury, progression of fibrosis, and promotion of fibrosis resolution. These features have made hepatic macrophages uniquely attractive therapeutic targets in the fight against hepatic fibrosis. In this review, we synthesised the literature to highlight the functions and regulation of heterogeneity in hepatic macrophages. Furthermore, using the existing findings, we attempt to offer insights into the molecular mechanisms underlying the phenotypic switch from fibrogenic macrophages to restorative macrophages, the regulation of heterogeneity, and modes of action for hepatic macrophages. A better understanding of these mechanisms may guide the development of novel anti‐fibrotic therapies (eg macrophage subset‐targeted treatments) to combat liver fibrosis in the future.